Vida académica y solidaridad. Valores y compromiso del profesor universitario (2007)
Faith and reason happen to be perfectly compatible in the academic sphere. The search for truth generates solidarity within the university community framework. In the face of the immanent naturalism of modernity or the nihilistic skepticism of postmodernity, the recovery of the human being is a key element in the reformulation of culture.